MULTIPLE EXPLANTATION, LOW-POWER LASER, AND VITAMIN B COMPLEX IN THE TREATMENT OF MANDIBULAR PARESTHESIA AND DYSESTHESIA: CASE REPORT - Diaz-Campos, Julissa Sarai (2025)
Neurosensory disorders (ND) following the placement of dental implants (DI) in the posterior mandibular region are a potential complication due to their proximity to the inferior alveolar nerve (IAN). Paresthesia and dysesthesia are the most commonly reported symptoms, affecting quality of life and requiring an effective therapeutic approach. This case report describes the management of ND using adjunctive laser therapy (LT) combined with B-complex vitamins (B-Vit). A 57-year-old female patient presented with persistent hypoesthesia and spontaneous episodes of electric shock-like sensations after the placement of three dental implants in the posterior right mandibular region. Clinical examination confirmed a lack of soft tissue sensation and pain rated 8/10 on the Visual Analog Scale (VAS) at the depth of the sulcus. Tomographic imaging revealed compression of the IAN by all three DI. A diagnosis of paresthesia with dysesthesia secondary to nerve compression was established. With informed consent, the dental implants were explanted, followed by guided bone regeneration. As adjunctive therapy, low-level laser therapy (LLLT) at wavelengths of 650 nm and 976 nm was applied, along with B-Vit administered every 8 hours for 15 days. By the third session, the patient reported recovered sensation and a pain score of 0/10 on the VAS, leading to the conclusion of treatment. Subsequent tomographic imaging showed the bone neoformation. This case suggests that the combination of LLLT with B-Vit may serve as an adjunctive therapeutic alternative for the management of dysesthesia and paresthesia following the explantation of implants compressing the IAN.